Different dissolved organic matters regulate the bioavailability of heavy metals and rhizosphere microbial activity in a plant-wetland soil system. Issue 6 (December 2021) - Li, Yuanhang; Gong, Xiaofeng; Xiong, Jieqian; Sun, Yuheng; Shu, Yao; Niu, Danni; Lin, Yuan; Wu, Li; Zhang, Ru
Abstract: Dissolved organic matter (DOM) and hydrologic conditions significantly influences the migration and transformation of heavy metals, especially in wetland soil. However, there still remains challenge in understanding how the DOM from different sources regulates the bioavailability of heavy metals, enzyme activity and microbial activity. In this study, we investigated the effects of natural DOM (NDOM, extraction of Carex cinerascens ) and artificial DOM (Humic acids, HA) on microbial community and bioavailability of Cu and Pb in wetland soils of Poyang Lake under wetted and flooded conditions. The results demonstrated that the pH increased from 5.5 to 6.4 while Eh decreased from 95.8 to 31.6 mV to maximum extent after applying HA under flooded condition. Although planting C. cinerascens improved the soil quality under the stress of Cu and Pb, the use of HA restrained this effect except for Pb under wetted condition, demonstrating the intake of exogenous DOM increased the bioavailability of metals under flooded condition. However, the activities of catalase and urease in soil were markedly enhanced due to the implication of DOM, which increased more under the wetted condition as compared to the flooded condition. Similar phenomenon was found in chlorophyll. In addition, microbial diversity and community could be promoted by the application of HA. Diethylenetriamine pentaacetic acid -Cu (DTPA-Cu), pH and flooded condition might significantly influence the bacterial composition. Therefore, this research presents valuable theoretical basis for remediation of heavy metals and effects of DOM and hydrologic condition on microorganism in plant-wetland soil system. Graphical Abstract: ga1 Highlights: The pH increased and the Eh decreased with adding NDOM or HA in acid soil. Adding HA increased the bioavailability of Cu and Pb in soil, except for Pb under wetted condition. Adding DOM significantly enhanced the soil enzymes activities and the content of chlorophyll a+b . Flooded condition, pH and DTPA-Cu were the key indicators affecting the rhizosphere microbial activity.